Transactivation of the minus-strand DNA transfer by nucleocapsid protein during reverse transcription of the retroviral genome. - Allain, B (1994)
Two DNA strand transfers are required during reverse transcription of the RNA genome of retroviruses to complete provirus synthesis. To understand more about the first strand transfer reaction, that of the minus-strand DNA from the 5' to the 3' end of the retroviral genome, we devised an in vitro system mimicking the Moloney murine leukemia virus reverse transcription process. Two RNAs corresponding to the 5' and 3' regions of the genome were used to perform reverse transcription assays. The role of the nucleocapsid protein NCp10, which is tightly bound to the genome in the virus, was investigated in this system as well as the requirement of the 5' and 3' terminal repeats (R sequences) and the poly(A) tail. The results show that NCp10 drastically enhances the strand transfer reaction and that interactions between reverse transcriptase, nucleocapsid protein and viral RNA may be important. Both R sequences are required for an efficient and accurate DNA strand transfer and the poly(A) tail facilitates this reaction. Furthermore, it is probable that both intra- and intermolecular DNA strand transfers occur when the 5' and 3' ends of the genome are present on the same molecule.